Motyw "starego winka" w "Śpiewce" Jakuba Jasińskiego = The motif of "old wine" in "Śpiewka" by Jakub Jasiński - Tomicka, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to show Jakub Jasiński`s poem "Śpiewka" in the context of the relationship between consumption of alcohol and the care of humor. The work has a bachic character, which was emphasized by analyzing its content and the structure of the poem. The text also includes a broad cultural context and biographical motifs of the poet. They bent over the motif of the "old wine bottle" in the poem as the leading role in the work.
Keywords: Jasiński, Jakub (generał; 1761-1794); "Śpiewka"; wino; 18 w.; wine